Thermal Model of a Smart Home - Orlova, Valeriia (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2025)
This paper focuses on developing a comprehensive thermal model of a selected smart home. Thermal behavior is derived from the 3D conceptual models of the house’s interior created in SolidWorks based on personal knowledge and available blueprints. Utilizing the information about individual structural elements, their dimensions, materials, and thermal properties available in the 3D models, a thermal model of the building is developed in MATLAB Simulink using the Simscape Thermal Models. The thermal model is tested under diverse conditions through a 24-hour operation simulation using the external temperature and irradiation data from geographic information systems.
Keywords: Airflow; conjugate heat transfer; heat transfer; home automation; HVAC systems; smart home; thermal behavior simulation; thermal comfort; thermal energy storage